Home security alarm system / Nur Laila Hamzah, Siti Fatimah Mohd Azhari and Mohamad Izzat Mohamad Zamri - Hamzah, Nur Laila; Mohd Azhari, Siti Fatimah; Mohamad Zamri, Mohamad Izzat (2013)
The purpose of this project is to develop an electronic based project which could act as a device that able to help people become vigilant of their home safety during lack the owner. This requirement has become a demanded as nowadays system are too dependent to the community. For the truth, people need to ‘on’ this device at all time for 24-hours safety. This device is using infrared alarm which works by infrared. Infrared is used as a sensor, from an infrared transmitter to the receiver. When infrared light are blocked by some movement, the alarm will activate a buzzer and LED will light up. As for result of our design expectation, it will give us LED blinking and alarm sound alert. Due to the significant of the project that is focusing on to develop a tool that can help to reduce the carelessness amongst users.